Characterization of the Leucocyte Immunoglobulin-like Receptor B4 (Lilrb4) Expression in Microglia - Felix Kretzschmar; Robin Piecha; Jannik Jahn; Phani Sankar Potru; Björn Spittau (Biology, 2021)
As resident innate immune cells of the CNS, microglia play important essential roles during physiological and pathological situations. Recent reports have described the expression of Lilrb4 in disease-associated and aged microglia. Here, we characterized the expression of Lilrb4 in microglia in vitro and in vivo in comparison with bone marrow-derived monocytes and peritoneal macrophages in mice. Using BV2 cells, primary microglia cultures as well as ex vivo isolated microglia and myeloid cells in combination with qPCR and flow cytometry, we were able to provide a comprehensive characterization of Lilrb4 expression in distinct mouse myeloid cells. Whereas microglia in vivo display low expression of Lilrb4, primary microglia cultures present high levels of surface LILRB4. Among the analyzed peripheral myeloid cells, peritoneal macrophages showed the highest expression levels of Lilrb4. Moreover, LPS treatment and inhibition of microglial TGFβ signaling resulted in significant increases of LILRB4 cell surface levels. Taken together, our data indicate that LILRB4 is a reliable surface marker for activated microglia and further demonstrate that microglial TGFβ signaling is involved in the regulation of Lilrb4 expression during LPS-induced microglia activation.